Automatic annotation of actigraphy data for sleep disorders diagnosis purposes - Domingues, Alexandre; Adamec, Ondřej; Paiva, Teresa; Sanches, J. Miguel (Conference proceedings ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2010)
The diagnosis of Sleep disorders, highly prevalent in the western countries, typically involves sophisticated procedures and equipments that are intrusive to the patient. Wrist actigraphy, on the contrary, is a non-invasive and low cost solution to gather data which can provide valuable information in the diagnosis of these disorders. The acquired data may be used to infer the Sleep/Wakefulness (SW) state of the patient during the circadian cycle and detect abnormal behavioral patterns associated with these disorders. In this paper a classifier based on Autoregressive (AR) model coefficients, among other features, is proposed to estimate the SW state. The real data, acquired from 23 healthy subjects during fourteen days each, was segmented by expert medical personal with the help of complementary information such as light intensity and Sleep e-Diary information. Monte Carlo tests with a Leave-One-Out Cross Validation (LOOCV) strategy were used to assess the performance of the classifier which achieves an accuracy of 96%.
Keywords: automatizované zpracování dat; poruchy spánku a bdění; aktigrafie; Reproducibility of Results; Sleep Wake Disorders; bdění; Bayesova věta; lidé; reprodukovatelnost výsledků; Actigraphy; spánek; Automation; Wakefulness; Bayes Theorem; automatizace; Sleep; Electronic Data Processing; Humans